Parallel Processor for 3D Recovery from Optical Flow. (24th November 2009) - Barron-Zambrano, Jose Hugo; Martin del Campo-Ramirez, Fernando; Arias-Estrada, Miguel
Abstract : 3D recovery from motion has received a major effort in computer vision systems in the recent years. The main problem lies in the number of operations and memory accesses to be performed by the majority of the existing techniques when translated to hardware or software implementations. This paper proposes a parallel processor for 3D recovery from optical flow. Its main feature is the maximum reuse of data and the low number of clock cycles to calculate the optical flow, along with the precision with which 3D recovery is achieved. The results of the proposed architecture as well as those from processor synthesis are presented.